Autofiction(s) et scandale - Jacobi, Claudia; Ott, Christine; Schönwälder, Lena (Romanische Studien Beihefte, 2022)
The reception history of the term autofiction, coined by Serge Doubrovsky in 1977 and strongly polarising since then, shows that autofictional writing has been used by numerous authors in the past decades as a possibility to give explosive insights into their lives on the one hand, but to refer to an indeterminable ""fictional"" part of their work on the other. The underlying interferences between fictional and factual narrative strategies seem to predestine autofiction for the representation and provocation of scandal. This volume brings together contributions that illuminate the relationship between autofiction and scandal from epistemological, literary-historical and reception-aesthetic perspectives and explore ethical questions of the demarcation between public and private space.